The future of global value chains: Key issues - Roger Strange (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
The COVID-19 pandemic has heightened concerns about the viability of GVCs. Globalization was already under threat, but the pandemic has exacerbated the effects of underlying trends in the world economy. This Perspective considers whether MNEs should forsake cost-efficiency and reconfigure their GVCs to put more emphasis on robustness and resilience.
Keywords: 330